Penggunaan Metode Bercerita Untuk Meningkatkan Keterampilan Berbicara Di Depan Kelas Pada Siswa Kelas III SDN Gudang - Apriyanti, Rizki; Rahayu, Rahma; Arianti, Anggun Dwi; Lukman, Wardah; Hopeman, Teofilus Ardian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low speaking skills of third-grade students at SDN Gudang, particularly in expressing ideas fluently and confidently in front of the class. The objective of this study was to improve students' speaking skills through the implementation of storytelling as an engaging and interactive learning approach. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, which consisted of three cycles. Each cycle included the stages of planning, action, observation, and reflection. The research subjects were 31 third-grade students. The instruments used included performance tests and observation checklists to assess speaking skills. The findings revealed a significant improvement in students’ speaking abilities across the cycles. The percentage of students achieving learning mastery increased from 16.1% in the pre-cycle to 87% in both the second and third cycles. The improvement encompassed fluency, self-confidence, and expressive ability. It can be concluded that storytelling is an effective method for enhancing students' speaking skills in primary education while also fostering motivation and active participation in the learning process.